KRT8 phosphorylation regulates the epithelial‐mesenchymal transition in retinal pigment epithelial cells through autophagy modulation. Issue 5 (5th February 2020) - Miao, Qi; Xu, Yufeng; Yin, Houfa; Zhang, Huina; Ye, Juan
Abstract: Proliferative vitreoretinopathy (PVR) is a severe ocular disease which results in complex retinal detachment and irreversible vision loss. The epithelial‐mesenchymal transition (EMT) of retinal pigment epithelial (RPE) cells is considered to be critical in the pathogenesis of PVR. In this study, we focused on the potential impact of keratin 8 (KRT8) phosphorylation and autophagy on TGF‐β2–induced EMT of RPE cells and explored the relationship between them. Using immunofluorescence and Western blot analysis, the co‐localization of KRT8 and autophagy marker, as well as the abundance of phosphorylated KRT8 (p‐KRT8) expression, was observed within subretinal and epiretinal membranes from PVR patients. Moreover, during TGF‐β2–induced EMT process, we found that p‐KRT8 was enhanced in RPE cells, which accompanied by an increase in autophagic flux. Inhibition of autophagy with pharmacological inhibitors or specific siRNAs was associated with a reduction in cell migration and the synthesis of several EMT markers. In the meantime, we demonstrated that p‐KRT8 was correlated with the autophagy progression during the EMT of RPE cells. Knockdown the expression or mutagenesis of the critical phosphorylated site of KRT8 would induce autophagy impairment, through affecting the fusion of autophagosomes and lysosomes. Therefore, this study may provide a new insight into the pathogenesis of PVR and suggests the potential therapeutic value of p‐KRT8 in the prevention and treatment of PVR.